Incidence and Associated Factors of Post-Transplant Erythrocytosis Following Kidney Transplantation - Siriphotjanakun, Thanachai; Phonphok, Korntip (Journal of the Nephrology Society of Thailand, 2025)
Background: Post-transplant erythrocytosis (PTE) is a persistent increase in red blood cell count following kidney transplantation. Patients with PTE face an increased thrombotic risk, which leads to higher morbidity and mortality. This retrospective cohort study aimed to identify the incidence and risk factors of PTE in kidney transplant recipients. Methods: A total of 286 kidney transplant recipients from 1998 to 2022 were included in the study. The diagnosis of PTE was based on hemoglobin levels >17 g/dL and/or hematocrit >51%. Baseline factors associated with PTE were analyzed using the Cox proportional hazards regression model. Results: PTE occurred in 26 (9.1%) patients, with a median onset of 7.1 months (4-41.6 months) post-transplantation. Male sex, a history of smoking, higher body mass index, higher pretransplant hematocrit, and absence of pretransplant renin-angiotensin-aldosterone system (RAAS) blockade were associated with the development of PTE. In multivariate analysis, only male sex and higher body mass index were independent predictors of PTE. Most patients responded well to RAAS blockade, with 7 (27%) patients experiencing spontaneous recovery, and 7 (27%) undergoing phlebotomy. Transplant renal artery stenosis was diagnosed in 3 (11%) patients. Conclusions: Nine percent of kidney transplant recipients developed PTE approximately seven months post-transplantation. Male sex and higher body mass index were identified as independent predictors of PTE. Most patients responded well to RAAS blockade, with a quarter experiencing spontaneous recovery.